Understanding physician behaviour in the 6–8 weeks hip check in primary care: a qualitative study using the COM-B. Issue 3 (19th March 2021) - Chater, Angel; Milton, Sarah; Green, Judith; Gilworth, Gill; Roposch, Andreas
Abstract : Objectives: A compulsory hip check is performed on an infant at 6–8 weeks in primary care for the detection of developmental dysplasia of the hip (DDH). Missed diagnoses and infants incorrectly labelled with DDH remain an important problem. The nature of physician behaviour as a likely source of this problem has not been explored. The aims of this study were to make a behavioural diagnosis of general practitioners (GPs) who perform these hip checks, and identify potential behavioural change techniques that could make the hip checks more effective. Design: Qualitative study with in-depth semistructured interviews of 6–8 weeks checks. We used the Capability, Opportunity, Motivation and Behaviour model in making a behavioural diagnosis and elicited factors that can be linked to improving the assessment. Setting: Primary care. Participants: 17 GPs (15 female) who had between 5 and 34 years of work experience were interviewed. Results: Capability related to knowledge of evidence-based criteria and skill to identify DDH were important behavioural factors. Both physical (clinic time and space) and social (practice norms), opportunity were essential for optimal behaviour. Furthermore, motivation related to the importance of the 6–8 weeks check and confidence to perform the check and refer appropriately were identified in the behavioural diagnosis. Conclusion: Aspects of capability, opportunity and motivation affect GPs' diagnosis and referral behaviours in relation to DDH. The findings from this work extend current knowledge and will inform the development of an intervention aimed at improving the diagnosis of DDH.